2015
DOI: 10.1002/nur.21675
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Heart Failure Self‐Care Maintenance and Management in Patients and Caregivers: A Dyadic Analysis

Abstract: Disease self-management is a critical component of maintaining clinical stability for patients with chronic illness. This is particularly evident in the context of heart failure (HF), which is the leading cause of hospitalization for older adults. HF self- management, commonly known as HF self-care, is often performed with the support of informal caregivers. However, little is known about how HF dyads manage the patient’s care together. The purpose of this study was to identify determinants of patient and care… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
115
2
16

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 112 publications
(138 citation statements)
references
References 61 publications
5
115
2
16
Order By: Relevance
“…As in an earlier study, 25 relationship quality was significantly related to dyads’ self-care. In that earlier study, however, relationship quality was measured by a 1-item question asking the person to judge how good their relationship was.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As in an earlier study, 25 relationship quality was significantly related to dyads’ self-care. In that earlier study, however, relationship quality was measured by a 1-item question asking the person to judge how good their relationship was.…”
Section: Discussionsupporting
confidence: 77%
“…This one item was linked to self-care maintenance and self-care management. 25 What our study suggests is that that self-care self-efficacy may be moderating the relationship between relationship quality and HF self-care, at least for the caregiver. The impact of the caregiver’s perception of the relationship on self-efficacy is supported in the literature.…”
Section: Discussionmentioning
confidence: 67%
“…One study identified poor caregiver health and higher strain as associated with patients having higher confidence in providing themselves self-care [86]. Similarly though in the opposite direction, in an Italian sample of 364 dyads, increased caregiver physical QoL was associated with lower levels of patient self-care management for male patients [37]; male patients who had healthier caregivers were less likely to personally attend to their self-care needs. The authors postulated that poorer self-care behaviors among male patients may be a function of poor symptom recognition.…”
Section: Resultsmentioning
confidence: 99%
“…From recent observational and interventional research, we know that caregivers play a major role in HF self-care, 31 that the patient-caregiver relationship influences self-care engagement, 32, 45, 46 and that dyadic interventions to improve self-care may be more efficacious than individual approaches. 47, 48 Thus, it is not surprising that caregiver self-care contributions significantly predicted patient event-free survival in this analysis.…”
Section: Discussionmentioning
confidence: 99%